The Effect of a Leadership Training Program on Consideration of Future Consequences. Issue 4 (April 2017) - Sadler, Theresa D.; Gibson, Shonda; Reysen, Stephen
Abstract : The effect of participation in a leadership training program on participants' consideration of immediate and future consequences was examined. Participants were randomly assigned to complete a leadership program or not during a college course. All participants completed measures of immediate and future consequences at the beginning and middle of the semester. The results showed no differences in degree of immediate concern between conditions. However, participants who completed the leadership program showed an increase in the consideration of future consequences ( d = −.19, confidence interval [CI] [−.301 to −.081]), while participants in the control condition did not ( d = .05, CI [−.046 to .142]). The results highlight the causal relationship between leadership training and individuals' focus on future consequences.